2020
DOI: 10.1002/nbm.4274
|View full text |Cite
|
Sign up to set email alerts
|

Wideband Self‐Grounded Bow‐Tie Antenna for Thermal MR

Abstract: The objective of this study was the design, implementation, evaluation and application of a compact wideband self-grounded bow-tie (SGBT) radiofrequency (RF) antenna building block that supports anatomical proton ( 1 H) MRI, fluorine ( 19 F) MRI, MR thermometry and broadband thermal intervention integrated in a wholebody 7.0 T system. Design considerations and optimizations were conducted with numerical electromagnetic field (EMF) simulations to facilitate a broadband thermal intervention frequency of the RF a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…For this purpose, eight arbitrary RF channels (four from each module of the signal generator) were used to generate 400 MHz RF signals using tailored amplitude and phase settings. The RF signals were connected to eight wideband self-grounded bow-tie (SGBT) antennae [ 23 ] immersed in deionized water. The SGBT antennae were arranged in a circular array.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For this purpose, eight arbitrary RF channels (four from each module of the signal generator) were used to generate 400 MHz RF signals using tailored amplitude and phase settings. The RF signals were connected to eight wideband self-grounded bow-tie (SGBT) antennae [ 23 ] immersed in deionized water. The SGBT antennae were arranged in a circular array.…”
Section: Methodsmentioning
confidence: 99%
“…HT devices are increasingly capable of the personalized radio frequency (RF)-induced heating of target tissue volumes guided by sophisticated treatment planning procedures and thermal dose control [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. Thermal Magnetic Resonance (ThermalMR) is an HT variant that accommodates RF-induced heating [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ], temperature mapping using MR thermometry (MRT) [ 26 , 27 , 28 , 29 ], anatomic and functional imaging and the option for x-nuclei MR imaging (MRI) in a single, multi-purpose RF applicator.…”
Section: Introductionmentioning
confidence: 99%
“…Later, Ipek et al [14] found that the optimal transmit field efficiency can be achieved for a block with 150 mm × 50 mm × 50 mm and ε r between 90 and 110. Recently, Eigentler et al [15] developed a self-grounded bowtie antenna, which was immersed in a small volume filled with deuterium oxide (D 2 O), but they used quite a large water bolus to ensure a direct contact with a cuboid phantom.…”
Section: Introductionmentioning
confidence: 99%
“…All these reports [6,[13][14][15] assumed there was a direct contact between the dielectric block and the human body (or a phantom with a flat surface). Yet, such a contact is rather difficult to achieve for a solid, rectangular geometry, and it may not always be feasible in clinical settings.…”
Section: Introductionmentioning
confidence: 99%
“…To apply heat into a target site, controlled manipulation of temperature is required while concomitantly characterizing its outcome in vivo. Here, we used thermal magnetic resonance (ThermalMR) that provides RF-induced temperature modulation, temperature monitoring using MR thermometry, anatomic reference, functional imaging, and (nano)molecular probing in an integrated RF applicator [ 29 , 30 , 33 ].…”
Section: Introductionmentioning
confidence: 99%